Electrochemical Characterization of the Interaction of Multiwalled Carbon Nanotubes with Doxorubicin. (22nd September 2017) - Moulick, Amitava; Milosavljevic, Vedran; Nguyen, Hoai Viet; Kopel, Pavel; Adam, Vojtech
ABSTRACT: It has been suggested that multiwalled carbon nanotubes (MWCNTs) interacting with pharmaceutics may be introduced into the body as nanocarriers. To deliver the anticancer drugs, covalent or noncovalent functionalization of MWCNTs is required. In this study, the influence of oxidation on MWCNTs in the interaction with chemotherapeutic drug, doxorubicin, was characterized. The binding of doxorubicin with MWCNTs decreased rapidly with the increasing oxidation period with sulfuric acid. However, with nitric acid, the interaction increased initially and slowly decreased with time. The best results were obtained for sulfuric and nitric acid following 1 and 3 h of oxidation, respectively. The results show that sulfuric acid provided more favorable interaction for MWCNTs with doxorubicin than nitric acid.